Comparative Study Of Solar Radiation On Clay Roof Tiles And Teki Grass-Based HDPE Composite Roof Tiles - Hamzah, Muhammad Fakhri; Fahrudin, Fahrudin; Wahyuni, Fitri; Martana, Budhi (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2024)
Along with the advancement of science and technology, various types of tiles one of them is the use of polymer composites as the main material for making tiles. Roof tiles are generally made of clay and metal. The high use of plastic in Indonesia causes high waste generation and environmental damage. Efforts to reduce the generation of plastic waste are by utilizing plastic waste into polymer composite tiles. The tile requirement is that it must be able to withstand solar heat radiation and rainwater. The purpose of this study was to determine the comparison of solar radiation values on clay tile aerial, pure HDPE tile and 20% teki grass reinforced HDPE composite tile given 5% alkaline treatment for 4 hours. The test was carried out using exposure to direct solar radiation with a tile angle of 30o. The test data was obtained on the composition of 20% teki grass, the temperature produced on the upper and lower surfaces of the tile tends to be lower than pure HDPE and the top surface of the composite tile has a difference of 0.6oC higher than clay tile but for the bottom surface has a difference of 1.3oC lower than clay tile. Based on the radiation rate of HDPE and 20% teki grass tiles have a higher value than clay tiles so that HDPE reinforced teki grass 20% of tiles can be used as alternative materials to replace clay tiles because they have good heat resistance.